Nutritive values of some edible flowers found in northern Thailand during the rainy season - K. Kantadoung (2018)
Flowers are parts of the Thai cultures as they are used in religious ceremonies, used as ornamental or consumed as food. During the rainy season, numerous plant species give flowers and Thai people have learnt to utilise them as food ingredients in seasonal meals. This research investigated the nutritive composition of 11 edible flowers consumed in northern Thailand, namely Alpinia malaccensis, Borassus flabellifer, Cassia fistula, Dipterocarpus costatus, Dolichandrone serrulata, Gardenia jasminoides, Gymnema inodorum, Hapaline benthamiana, Peliosanthes teta, Sesbania grandiflora, and Tamarindus indica. The flowers were also examined for bioactive compounds and antioxidant potential. The results suggested that flowers were consumed either fresh, boiled or steam cooked. Their nutritive properties obtained were as follows; moisture contents (79.18-96.40%), crude proteins (0.83-3.83%), crude fibres (0.13-3.08%), ash (0.24-1.68%), carbohydrates (1.52-15.37%), crude lipids (0.16-1.77%), and food energy (13.81-73.07 kcal 100 g-1). The mineral elements contents were exceptional with potassium ranging from 101-657 mg 100 g-1, calcium from 27-218 mg 100 g-1, and sodium from 0.01-0.04 mg 100 g-1. These flowers also contained vitamin C (0.03-45.00 mg 100 g-1), polyphenols (0.14-16.81 mg GAE g-1 extract), and flavonoids (6.17-44.17 mg RE g-1 extract) with antioxidant potential as high as 87.85% by DPPH radical scavenging activity and 118.45 mg TEAC g-1 extract by ABTS radical scavenging activity. The results indicate that these edible flowers can contribute substantially to the nutritional requirement for good health and well-being when consumed in adequate amounts.